Agglomeration tendencies in EU regions: where does capital go? - Claudia Stirböck (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper focuses on two aspects being neglected in the analysis of agglomeration tendencies so far. First, it regards regional agglomeration patterns and secondly, the allocation of capital across industrial sectors. Indeed, the average relative concentration of capital turns out to be of a higher level and variability than the one of employment in 1985-94. Regions marked by a relatively high uneven allocation of capital are also subject to lower economic performance than regions marked by a relatively low capital concentration. Though direct investments in services represent a large share of direct investments in the 1990s, relative specialisation in services is rather low, but steadily increasing from 1985-94 in EU countries and regions.
Keywords: E22; R30; F21; 330; Regional Economics; Direct Investment; Capital Allocation; Factor Mobility; Ballungsraum; Direktinvestition; Regionale Konzentration; Internationale Arbeitsteilung; Regionale Arbeitsteilung; EU-Staaten